Evaluasi dan Inovasi Manajemen Pembelajaran Bahasa Indonesia di Era Kurikulum Merdeka - Fatmawaty (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2025)
This study aims to analyze the management of Indonesian language learning in the Era of the Independent Curriculum: Evaluation and Innovation. This type of research is a literature review. A literature review is a systematic approach to assessing and synthesizing literature related to specific research topics or issues. It involves analyzing conceptual information as well as qualitative and quantitative data from previously published scholarly articles. Based on the findings and discussion, the use of technology and digital media in Indonesian language learning not only makes the learning process more engaging but also supports students in developing 21st-century skills, which are crucial in the modern era, including critical thinking, creativity, and digital literacy. This applies to both primary and secondary education, which generally face similar challenges. Such an approach makes Indonesian language learning more relevant, dynamic, and interactive, creating a motivating learning atmosphere that fosters student development. By emphasizing collaboration, critical thinking skills, and digital literacy, this method not only helps students understand Indonesian language technically but also enhances their communication skills in line with the demands of the modern world. Students are encouraged to become more critical, creative, and adaptive communicators in an ever-changing environment, while also understanding language in a global and digital context. Furthermore, formative assessment through portfolio-based approaches focuses on the individual development of students, encouraging them to become more reflective, independent, and creative learners. This approach allows students to grow at their own pace and according to their needs, while still receiving support and feedback from teachers. These strategies create an inclusive, adaptive, and supportive learning environment, ensuring students’ long-term success. The gap between the vision of the Merdeka Curriculum and the reality in the field can be addressed through several measures, such as intensive and continuous training, providing training focused on technology and innovative learning on a regular basis, and ensuring it aligns with the needs of Indonesian language teachers.